Possibilities of ultrasound in perioperative medicine. A tribute to fashion or the need for clinical search for a surgeon? (Perioperaciina Medicina, 2019)
This article discusses the possibilities of ultrasound in perioperative medicine, namely in the ultrasound study of the superficial organs, lungs, thyroid gland and other internal organs. This article presents sonograms of interest and rare clinical cases that may occur in the daily clinical practice of a surgeons. The article suggests that ultrasound method has an additional clinical value to establish and clarify the diagnosis in the practice of the surgeon. Studying the methods of ultrasound by surgeons will not only increase the efficiency of clinical thinking, but also reduce the time for establishing an accurate diagnosis and, consequently, choosing the optimal surgical treatment strategy for patients.
Keywords: Ultrasound; lymphadenitis; hematoma; surgical pathology